Dates Pits Activated Carbon as Cheap Sorbent for the Decontamination of the Cadmium Ions in Battery Mills Wastewater - Khalaf, Haya Kahtan; Rashid, Hayder M. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
In the current study, a novel date pit activated carbon, an environmentally friendly adsorbent, was, chemically activated by phosphoric acid, and employed as a bio-sorbent for Cd2+ adsorption from a simulated polluted solution. Utilizing a variety of characterization techniques, the surface morphology and functional groups of manufactured activated carbon and raw date pits are identified. The prepared activated carbon had an adsorption surface area and pore diameter values of 1700 m2/g and 3.78 nm, and this indicated the greatest increase in surface area. The effect of pH, initial Cd2+ concentration, contact time, and operating temperature on Cd2+ removal by date pit activated carbon was studied. A higher Cd2+ adsorption capacity of 48.34 mg/g was attained for a contact time of 240 min, initial concentration of 100 mg/L, and pH of 6 at 30 °C. The efficacy of Cd2+ adsorption on date pit activated carbon improved as the initial pH of the adsorbate increased to 6 and Cd2+ concentration decreased. At a given temperature of 30 °C, the Freundlich isotherm demonstrated to be the most adaptable one, indicating multilayer coverage with a 41.15 mg/g maximum adsorption capacity. For sorption favorability, the separation factor has been within the range of 0.001 to 0.003. Subsequently, the results demonstrated that the removal efficiency was adversely impacted by the rise in treatment temperature from 30 to 40 °C.